2020
DOI: 10.1016/j.neurol.2019.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Functional movement disorders

Abstract: Purpose of reviewThe review highlights the clinical presentation of functional movement disorders (FMDs) and presents current evidence on bedside signs and paraclinical tests to differentiate them from other neurological disorders. Recent findingsFMDs are diagnosed by the presence of positive clinical signs as emphasized in the new Diagnostic and Statistical Manual of Mental Disorders-5 classification criteria. Bedside signs are numerous, and a subset of them has been validated in controlled studies. This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…Various studies reported that the most common presentations of FMD were tremor (40.6–50% of FMD patients) and dystonia (17.2–18%), with parkinsonism, tics, myoclonus and chorea being less common ( 3 , 21 24 ). Our results confirmed functional dystonia and tremor as the most frequent symptoms, both initially (67 and 26%, respectively), and at final examination (71 and 36% patients, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies reported that the most common presentations of FMD were tremor (40.6–50% of FMD patients) and dystonia (17.2–18%), with parkinsonism, tics, myoclonus and chorea being less common ( 3 , 21 24 ). Our results confirmed functional dystonia and tremor as the most frequent symptoms, both initially (67 and 26%, respectively), and at final examination (71 and 36% patients, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical features of FMD, including paroxysmal onset, waxing, and waning course, migration of symptoms to different body parts, together with possible symptom replacement (the resolution of one symptom can be followed by the appearance of another) ( 3 ), speak in favor of the unpredictable and often elusive nature of such disorders, leaving both patients and their physicians in the field of uncertainty. Furthermore, additional physical features (such as pain, fatigue, bladder, or bowel problems, etc), as well as psychiatric comorbidities, are usually associated with FND/FMD and can have significant impact on outcome ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The DSM-5 added a clinical criterion in 2013, which allows a ''rule-in'' procedure in firming a diagnosis of FMDs so that it is no longer considered a diagnosis of exclusion. 2 Functional movement disorders account for even 15% of neurology outpatient clinics, which are more common in women 1,2 and range from 17 to 83 years old. 1 The incidence of functional neurological disorders is 4 to 12 of 100,000 per year.…”
Section: The Pretender Of Parkinson's Disease: What Neurologists Need To Know About Functional Movement Disordersmentioning
confidence: 99%
“…Functional movement disorders (FMDs) comprise a broad range of clinical symptoms not explained by a classical neurological disease. Tremor is the most common symptom in FMDs 1 , 2 followed by dystonia, myoclonus, balance disorder, bradykinesia, cranial movement, hemifacial spasms, restless legs, and so on. FMDs are often categorized as “psychogenic,” and the psychological parkinsonism is about 10% of patients with FMDs.…”
mentioning
confidence: 99%
See 1 more Smart Citation